Factors That Affect Employee Satisfaction of Rsi Sultan Agung Banjarbaru South Kalimantan - Dewi Ariefahnoor; Ridha Setina Arini (Brilliant International Journal Of Management And Tourism, 2025)
With high work morale, it will create outstanding employees where work can be completed quickly, absenteeism can be minimized, damage can be reduced and the possibility of employee transfer to another company can be minimized. Work morale and job satisfaction greatly affect the achievement of company goals. If in a company the level of work morale and productivity is low, the company will experience many difficulties and even the company can go out of business if it is not dealt with immediately. RSI Sultan Agung which reads "A leading Islamic education hospital in health services, education and the development of Islamic civilization, towards a prosperous healthy society blessed by Allah" The mission of RSI Sultan Agung is "to organize health services that are safe and save in the spirit of loving Allah to love others, organizing educational services in order to build a generation of khaira ummah, and building Islamic civilization towards a prosperous healthy society which is blessed by Allah. The research design used is a quantitative analytical descriptive design that aims to describe the nature and characteristics of the data or variables to be tested, so that in this study it is used to analyze the data obtained, so that the influence between independent and bound variables can be known. The results of the data analysis indicated that the variables of compensation, work characteristics and work morale, simultaneously had a significant influence on the level of job satisfaction of employees of the Sultan Agung Islamic Hospital Banjarbaru. This means that the high and low level of employee job satisfaction has been greatly influenced by these three variables. This is also emphasized by the value of the determination coefficient  of the Adjusted R Square  result in the first regression = 0.437, meaning that the size of the ability of the X variable, namely Compensation (X1), Job Characteristics (X2) and Work Spirit (X3) in explaining the job satisfaction level of employees of the Sultan Agung Islamic Hospital Banjarbaru is 43.7%.